Maternal mental health concerns during the COVID-19 pandemic in Iran: a content analysis study - Pouran Mokhtari Zanjani; Najmeh Tehranian; Nasrin Changizi; Eesa Mohammadi; Banafsheh Farzinrad; Anoshirvan Kazemnejad (BMC, 2023)
Abstract Background As crises occur, attention to physical health usually becomes more than mental health, neglecting mental health, especially in some vulnerable groups such as pregnant women and new mothers, can have adverse consequences. Therefore, it is imperative to recognize and comprehend their mental health needs, particularly during critical situations such as the recent COVID-19 pandemic. The aim of this study was to explain the understanding and experience of mental health concerns faced by pregnant and postpartum women during this pandemic. Methods This qualitative study was conducted from March 2021 to November 2021 in Iran. Data were collected using semi-structured in-depth interviews to understand mental health concerns in pregnancy and the postpartum period during the COVID-19 pandemic. Twenty-five purposefully retrieved and participated in the study. Due to the prevalence of coronavirus, most of the participants preferred tele interviews. When data saturation was achieved, the data were codified manually and analyzed using Graneheim and Lundman's approach 2004. Results Based on the content analysis of the interviews, 2 main themes, 8 categories 23 subcategories were identified. The identified themes were as follows: (1) Maternal mental health threats and (2) Inadequate access to the required information. Conclusion The results of this study showed that the main concern and fear of pregnant and postpartum women in the COVID-19 pandemic was the fear of the possibility of death for themselves and/or their fetus/infant. The knowledge that was obtained from the understanding of pregnant women and new mothers about the mental health concerns during the COVID-19 pandemic can help managers in planning to improve and promote women's mental health, especially in critical situations.